A high heat-resistant and high-barrier PA6 / COC composite material and preparation method thereof

By introducing COC resin and nucleating agent into PA6 material, combined with toughening agent and lubricant, the water absorption and heat resistance of PA6 material is solved, and a PA6/COC composite material with high heat resistance and high barrier is achieved.

CN119119724BActive Publication Date: 2025-03-11POLYSTAR ENG PLASTICS (SHANGHAI) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411587660.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-11
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The existing PA6 materials have the disadvantages of large water absorption, poor dimensional stability, and poor acid and alkali resistance. In addition, ordinary polyolefin resins have poor heat resistance, making it difficult to meet the needs of high heat resistance and high barriers.

Method used

High viscosity PA6 is used as the first matrix resin and COC is used as the second matrix resin. The solvent resistance of PA6 is improved through COC, and the crystallinity and performance of the material are added to improve the material's crystallinity and performance. At the same time, an appropriate toughening agent and lubricant system is used to balance the rigidity, toughness and processing properties of the material.

Benefits of technology

It realizes high heat resistance, excellent solvent resistance and good barrier properties of PA6/COC composite materials, and improves the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides a high heat-resistant and high-barrier PA6 / COC composite material and a preparation method thereof, wherein the PA6 / COC composite material comprises the following components by weight: 65-80 parts of PA6; 15-25 parts of COC; 6-10 parts of modified filler; 0.5-1.5 parts of nucleating agent; 4-8 parts of toughening agent; 0.5-2 parts of lubricant; 0.2-1.0 parts of antioxidant. The present invention adopts high-viscosity PA6 as the first matrix resin and COC as the second matrix resin, improves the solvent resistance of PA6 by COC, adds a nucleating agent to improve the crystallinity of the alloy material, further improves the rigidity, heat resistance, solvent resistance and barrier properties of the material, and adopts an appropriate toughening agent and lubricant system to balance the rigidity, toughness and processing properties of the material, so that the finally prepared PA6 / COC composite material has high heat resistance, excellent solvent resistance and good barrier properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer material modification and relates to a high-heat-resistant and high-barrier PA6 / COC composite material and a preparation method thereof. Background Art

[0002] Polyamide (PA), commonly known as nylon, is a heterochain polymer containing an amide group (-NHCO-) ​​in the main chain. It can be divided into two categories: aliphatic and aromatic. It is the earliest developed and most widely used thermoplastic engineering material. Polyamide-6 (PA6) is an aliphatic polyamide with excellent properties such as light weight, high strength, wear resistance, resistance to weak acids and alkalis and some organic solvents, and easy molding and processing. It is widely used in the fields of fibers, engineering plastics and films. However, the molecular chain segments of PA6 contain highly polar amide groups, which easily form hydrogen bonds with water molecules. The product has the disadvantages of high water absorption, poor dimensional stability, low impact strength in dry state and at low temperature, and poor resistance to strong acids and alkalis. After reasonable modification, it is widely used in various fields of automobiles, such as pipelines, buckles, door handles and other parts.

[0003] COC is a cyclic olefin copolymer. Different from crystalline polyolefins represented by polyethylene and polypropylene, it is an engineering plastic whose main molecular chain is composed of carbon and hydrogen through high crystallization to form a compact crystalline structure. This structure gives the polymer excellent chemical resistance, impact resistance, friction performance and high barrier properties.

[0004] Most of the materials used in fuel vehicles, hybrid vehicles and electric vehicles are made of nylon. In order to improve the solvent resistance and barrier properties of nylon, most modification methods use non-polar polyolefin resins for modification. However, ordinary polyolefin products, such as polyethylene and polypropylene, have low melting points and poor heat resistance. In order to improve this heat resistance problem, the present invention introduces a COC product with high barrier and good heat resistance, modifies COC, and selects a suitable lubricant to improve the processing problem of the material, and finally obtains a high heat resistance and high barrier PA6 / COC composite material. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a PA6 / COC composite material and a preparation method thereof. The present invention adopts high-viscosity PA6 as the first matrix resin and COC as the second matrix resin, improves the solvent resistance of PA6 by COC, adds a nucleating agent to improve the crystallinity of the alloy material, further improves the rigidity, heat resistance, solvent resistance and barrier properties of the material, and adopts an appropriate toughening agent and lubricant system to balance the rigidity, toughness and processing properties of the material, so that the finally prepared PA6 / COC composite material has high heat resistance, excellent solvent resistance and good barrier properties.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a PA6 / COC composite material, which comprises the following components by weight: 65-80 parts of PA6; 15-25 parts of COC; 6-10 parts of modified filler; 0.3-0.8 parts of nucleating agent; 4-8 parts of toughening agent; 0.5-2 parts of lubricant; and 0.2-1.0 parts of antioxidant.

[0008] As a preferred embodiment of the present invention, the preparation method of the modified filler comprises the following steps:

[0009] (1) Alumina, titanium dioxide and silicon dioxide are mixed in a weight ratio of 1:0.4-0.6:1.5-1.7 to obtain a filler; the particle size of the aluminum oxide is 60-100 nm, and the specific surface area is 20-30 m2 / g; the particle size of the titanium dioxide is 30-50 nm, and the specific surface area is 15-30 m2 / g; the particle size of the silicon dioxide is 10-20 nm, and the specific surface area is 200-250 m2 / g;

[0010] (2) Under a nitrogen atmosphere, 3 parts by mass of polyethyleneimine and 8-10 parts by mass of water are mixed to obtain a polyethyleneimine aqueous solution, and the polyethyleneimine aqueous solution is mixed with 1-1.5 parts by mass of a filler, stirred at 60-65° C. for 5-6 hours, centrifuged, and dried to obtain a modified filler.

[0011] As a preferred solution of the present invention, the intrinsic viscosity of the PA6 is above 3.0; the melt index of the COC is 10g / 10min-20g / 10min, and the test conditions are 260°C and 2.16kg.

[0012] As a preferred solution of the present invention, the content of MAH and GMA in the toughening agent is above 5%.

[0013] As a preferred embodiment of the present invention, the antioxidant includes one or a combination of any of 2,6-di-tert-butyl-p-cresol, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tris(nonylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, dioctadecyl pentaerythritol diphosphite, dilauryl thiodipropionate, and pentaerythritol stearate.

[0014] As a preferred embodiment of the present invention, the lubricant includes any one of oxidized polyethylene wax, ethylene-propylene copolymer, and ethylene-vinyl acetate copolymer, or a combination of at least two thereof.

[0015] As a preferred embodiment of the present invention, the nucleating agent includes P22 or CHB-3C.

[0016] In a second aspect, the present invention provides a method for preparing the aforementioned PA6 / COC composite material, the preparation method comprising the following steps:

[0017] The formulated amounts of PA6, COC, modified filler, toughening agent, lubricant, antioxidant and nucleating agent are mixed in a high-speed mixer to obtain a mixture, and the mixture is fed from a main feeding port of a twin-screw extruder to perform extrusion granulation.

[0018] As a preferred solution of the present invention, the mixing time is 3 min-7 min.

[0019] As a preferred solution of the present invention, the ratio of the screw length to the screw diameter of the twin-screw extruder is 30-48; the control temperature of each section of the twin-screw extruder is 250° C.-270° C., and the rotation speed is 240 rpm-320 rpm.

[0020] As a preferred solution of the present invention, after extrusion granulation, the obtained particles are dried and then injection molded into standard specimens for testing using an injection molding machine; wherein the drying temperature is 100-120°C and the drying time is 4-6h; the control temperature of each section of the injection molding machine is 250°C-270°C, and the screw speed is set to 100rpm-150rpm.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The present invention adopts high-viscosity PA6 as the first matrix resin and COC as the second matrix resin, improves the solvent resistance of PA6 by COC, adds a nucleating agent to improve the crystallinity of the alloy material, further improves the rigidity, heat resistance, solvent resistance and barrier properties of the material, and adopts an appropriate toughening agent and lubricant system to balance the rigidity, toughness and processing properties of the material, so that the finally prepared PA6 / COC composite material has high heat resistance, excellent solvent resistance and good barrier properties.

[0023] 2. The present invention adds modified fillers to the system. The introduction of nanofillers can form tiny stress concentration points, promote the uniform strengthening of the matrix, and increase the modulus of the material at the same time, thereby improving the tensile strength. The filler surface modified by PEI can improve the compactness of the composite material, reduce the chance of solvent molecules entering the interior of the material, thereby reducing the destructive effect of the solvent on the material structure. Through the above-mentioned modification treatment, the filler can not only be evenly dispersed in the matrix, but also form a good interface with the matrix, thereby enhancing the overall performance of the composite material. The addition of this modified filler not only improves the mechanical properties (such as tensile strength) of the composite material, but also enhances its aging resistance, especially in terms of solvent aging resistance.

[0024] 3. The present invention can improve the flexural modulus of the composite material by adding nanofillers with specific parameters and proportions. The specific particle size and specific surface area of ​​nano-scale alumina, titanium dioxide and silicon dioxide used in the present invention can provide more contact points and enhance the interaction between the matrix and the filler. The use of polyethyleneimine (PEI) under this condition is to improve the interfacial compatibility between the filler and the PA6 matrix. PEI can better form a protective film by adsorption on the surface of the filler, thereby improving the dispersibility of the filler in the matrix. The presence of nanofillers with specific parameters can serve as a reinforcing phase, and through the strong interaction between the filler and the matrix, the rigidity of the composite material is improved, thereby increasing the flexural modulus. By accurately controlling the particle size and specific surface area of ​​the filler, as well as appropriate surface treatment, the uniform dispersion of the filler in the matrix can be achieved, avoiding the performance degradation caused by local aggregation. DETAILED DESCRIPTION

[0025] In order to better illustrate the present invention and facilitate understanding of the technical solution of the present invention, the present invention is further described in detail below. However, the following embodiments are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0026] The specific implementation of the present invention provides a PA6 / COC composite material, which comprises the following components by weight: 65-80 parts of PA6; 15-25 parts of COC; 6-10 parts of modified filler; 0.3-0.8 parts of nucleating agent; 4-8 parts of toughening agent; 0.5-2 parts of lubricant; 0.2-1.0 parts of antioxidant;

[0027] The preparation method of the modified filler comprises the following steps:

[0028] (1) Alumina, titanium dioxide and silicon dioxide are mixed in a weight ratio of 1:0.4-0.6:1.5-1.7 to obtain a filler; the particle size of the aluminum oxide is 60-100 nm, and the specific surface area is 20-30 m2 / g; the particle size of the titanium dioxide is 30-50 nm, and the specific surface area is 15-30 m2 / g; the particle size of the silicon dioxide is 10-20 nm, and the specific surface area is 200-250 m2 / g;

[0029] (2) Under a nitrogen atmosphere, 3 parts by mass of polyethyleneimine and 8-10 parts by mass of water are mixed to obtain a polyethyleneimine aqueous solution, and the polyethyleneimine aqueous solution is mixed with 1-1.5 parts by mass of a filler, stirred at 60-65° C. for 5-6 hours, centrifuged, and dried to obtain a modified filler.

[0030] Among them, the weight of PA6 can be 66 parts, 68 parts, 70 parts, 72 parts, 74 parts, 76 parts, 78 parts, 80 parts, etc., but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the weight of COC can be 15 parts, 17 parts, 20 parts, 23 parts or 25 parts, etc., but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the weight of the toughening agent can be 4.0 parts, 5.0 parts, 6.0 parts, 7.0 parts or 8.0 parts, etc., but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the weight of the lubricant can be 4.0 parts, 5.0 parts, 6.0 parts, 7.0 parts or 8.0 parts, etc., but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; The weight portion of the antioxidant may be 0.2, 0.4, 0.6, 0.8 or 1.0, but is not limited to the values ​​listed. The weight portion of the nucleating agent may be 0.3, 0.4, 0.5, 0.6, 0.7 or 0.8, but is not limited to the values ​​listed. The weight portion of the nucleating agent may be 0.3, 0.4, 0.5, 0.6, 0.7 or 0.8, but is not limited to the values ​​listed. The weight portion of the nucleating agent may be 0.3, 0.4, 0.5, 0.6, 0.7 or 0.8, but is not limited to the values ​​listed.

[0031] As a preferred solution of the present invention, the PA6 is high-viscosity PA6 with an intrinsic viscosity of 4.0.

[0032] As a preferred solution of the present invention, the melt index of the COC is 10g / 10min-20g / 10min.

[0033] As a preferred solution of the present invention, the toughening agent is an E-GMA-MAH copolymer product.

[0034] As a preferred embodiment of the present invention, the lubricant is ethylene-vinyl acetate copolymer.

[0035] As a preferred embodiment of the present invention, the antioxidant is dioctadecyl pentaerythritol diphosphite.

[0036] As a preferred solution of the present invention, the nucleating agent is P22.

[0037] The specific embodiments of the present invention also provide a method for preparing the aforementioned PA6 / COC composite material, the method comprising the following steps:

[0038] The formulated amounts of PA6, COC, modified filler, toughening agent, lubricant, antioxidant and nucleating agent are mixed in a high-speed mixer, and the mixture is fed from a main feeding port of a twin-screw extruder for extrusion granulation.

[0039] As a preferred embodiment of the present invention, the mixing time is 3 min-7 min, for example, 3 min, 4 min, 5 min, 6 min or 7 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] As a preferred embodiment of the present invention, the ratio of the screw length L and the screw diameter D of the twin-screw extruder is 40-48, for example, 40, 41, 42, 43, 44, 45, 46, 47 or 48, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable, preferably 48; starting from the side feeding section, the threaded elements in the screw of the twin-screw extruder do not use strong shear threaded elements; the control temperature of each section of the twin-screw extruder is 250°C-270°C, for example, 250°C, 260°C or 270°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the rotation speed is 240rpm-320rpm, for example, 250rpm, 260rpm, 280rpm, 300rpm or 320rpm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0041] As a preferred embodiment of the present invention, after extrusion granulation, the obtained particles are dried and then injection molded into standard specimens for testing using an injection molding machine; wherein the drying temperature is 100-120°C, for example, 100°C, 105°C, 110°C, 115°C or 120°C, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the drying time is 4-6h, for example, 4h, 5h or 6h, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. Applicable; the control temperature of each section of the injection molding machine is 250°C-270°C, for example, 250°C, 260°C or 270°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the screw speed is set to 100rpm-1500rpm, for example, 100rpm, 110rpm, 120rpm, 130rpm, 140rpm or 150rpm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0042] The raw materials of the following examples were purchased from the following manufacturers:

[0043] The manufacturers of materials used in the examples of the present invention are as follows:

[0044] PA6: The relative viscosity of the PA6 is 4.0, COC (Mitsui Chemicals); (BASF);

[0045] COC: The melt index of COC is 15g / 10min; (Mitsui Chemicals);

[0046] Toughener: the toughener E-GMA-MAH (BF-7M), (Sumitomo Chemical);

[0047] Antioxidant: PETS (Kain Chemical),

[0048] Lubricant: ethylene-vinyl acetate copolymer (Honeywell); the viscosity of the ethylene-vinyl acetate copolymer at 100° C. is 600 cps, and the acid value is 11 mgKOH / g.

[0049] Nucleating agent: P22 (BASF).

[0050] Polyethyleneimine: viscosity 2200-15800 (mPa.s-25℃); GBK-PEI7 series.

[0051] The particle size of alumina is 60-100nm, and the specific surface area is 20-30㎡ / g; Zhejiang Zhiti Nano New Materials Co., Ltd.

[0052] The particle size of titanium dioxide is 30-50nm, and the specific surface area is 15-30㎡ / g; Zhejiang Zhiti Nano New Materials Co., Ltd.

[0053] The particle size of silicon dioxide is 10-20nm, and the specific surface area is 200-250㎡ / g; Zhejiang Zhiti Nano New Materials Co., Ltd.

[0054] Example 1

[0055] The present embodiment provides a PA6 / COC composite material, which comprises the following components by weight: PA6: 78 parts; COC: 15 parts; toughening agent: 5.0 parts; lubricant: 1.0 parts; antioxidant: 0.6 parts; modified filler: 7 parts; and nucleating agent: 0.4 parts.

[0056] The preparation method of the modified filler comprises the following steps:

[0057] (1) Alumina, titanium dioxide and silicon dioxide are mixed in a weight ratio of 1:0.5:1.6 to obtain a filler; the particle size of the aluminum oxide is 60-100 nm, and the specific surface area is 20-30 m2 / g; the particle size of the titanium dioxide is 30-50 nm, and the specific surface area is 15-30 m2 / g; the particle size of the silicon dioxide is 10-20 nm, and the specific surface area is 200-250 m2 / g;

[0058] (2) Under a nitrogen atmosphere, 3 parts by mass of polyethyleneimine and 9 parts by mass of water were mixed to obtain a polyethyleneimine aqueous solution. The polyethyleneimine aqueous solution was mixed with 1.2 parts by mass of a filler, stirred at 63° C. for 5.5 h, centrifuged, and dried to obtain a modified filler.

[0059] The preparation method of the composite material is as follows:

[0060] The formulated PA6 and COC, modified filler, toughening agent, lubricant, antioxidant and nucleating agent were mixed in a high-speed mixer for 4 minutes and then fed from the main feeding port of the twin-screw extruder, and the hollow glass microspheres were fed from the side feeding port of the twin-screw extruder. The temperature setting temperatures of each section of the twin-screw extruder were: 250°C, 250°C, 255°C, 255°C, 255°C, 260°C, 260°C, 265°C, 265°C, 260°C, the screw speed was set to 280rpm, the ratio of screw length L to screw diameter D was 48, and extrusion granulation was carried out to obtain a PA6 / COC composite material.

[0061] Example 2

[0062] The present embodiment provides a PA6 / COC composite material, which comprises the following components by weight: PA6: 73 parts; COC: 20 parts; toughening agent: 5.0 parts; lubricant: 1.0 parts; antioxidant: 0.6 parts; modified filler: 7 parts; and nucleating agent: 0.4 parts.

[0063] The preparation method of the modified filler comprises the following steps:

[0064] (1) Alumina, titanium dioxide and silicon dioxide are mixed in a weight ratio of 1:0.5:1.6 to obtain a filler; the particle size of the aluminum oxide is 60-100 nm, and the specific surface area is 20-30 m2 / g; the particle size of the titanium dioxide is 30-50 nm, and the specific surface area is 15-30 m2 / g; the particle size of the silicon dioxide is 10-20 nm, and the specific surface area is 200-250 m2 / g;

[0065] (2) Under a nitrogen atmosphere, 3 parts by mass of polyethyleneimine and 9 parts by mass of water were mixed to obtain a polyethyleneimine aqueous solution. The polyethyleneimine aqueous solution was mixed with 1.2 parts by mass of a filler, stirred at 63° C. for 5.5 h, centrifuged, and dried to obtain a modified filler.

[0066] The preparation method of the composite material is as follows:

[0067] The formulated PA6 and COC, modified filler, toughening agent, lubricant, antioxidant and nucleating agent were mixed in a high-speed mixer for 4 minutes and then fed from the main feeding port of the twin-screw extruder, and the hollow glass microspheres were fed from the side feeding port of the twin-screw extruder. The temperature setting temperatures of each section of the twin-screw extruder were: 250°C, 250°C, 255°C, 255°C, 255°C, 260°C, 260°C, 265°C, 265°C, 260°C, the screw speed was set to 280rpm, the ratio of screw length L to screw diameter D was 48, and extrusion granulation was carried out to obtain a PA6 / COC composite material.

[0068] Example 3

[0069] The present embodiment provides a PA6 / COC composite material, which comprises the following components by weight: PA6: 68 parts; COC: 25 parts; toughening agent: 5.0 parts; lubricant: 1.0 parts; antioxidant: 0.6 parts; modified filler: 7 parts; nucleating agent: 0.4 parts.

[0070] The preparation method of the modified filler comprises the following steps:

[0071] (1) Alumina, titanium dioxide and silicon dioxide are mixed in a weight ratio of 1:0.5:1.6 to obtain a filler; the particle size of the aluminum oxide is 60-100 nm, and the specific surface area is 20-30 m2 / g; the particle size of the titanium dioxide is 30-50 nm, and the specific surface area is 15-30 m2 / g; the particle size of the silicon dioxide is 10-20 nm, and the specific surface area is 200-250 m2 / g;

[0072] (2) Under a nitrogen atmosphere, 3 parts by mass of polyethyleneimine and 9 parts by mass of water were mixed to obtain a polyethyleneimine aqueous solution. The polyethyleneimine aqueous solution was mixed with 1.2 parts by mass of a filler, stirred at 63° C. for 5.5 h, centrifuged, and dried to obtain a modified filler.

[0073] The preparation method of the composite material is as follows:

[0074] The formulated PA6 and COC, modified filler, toughening agent, lubricant, antioxidant and nucleating agent were mixed in a high-speed mixer for 4 minutes and then fed from the main feeding port of the twin-screw extruder, and the hollow glass microspheres were fed from the side feeding port of the twin-screw extruder. The temperature setting temperatures of each section of the twin-screw extruder were: 250°C, 250°C, 255°C, 255°C, 255°C, 260°C, 260°C, 265°C, 265°C, 260°C, the screw speed was set to 280rpm, the ratio of screw length L to screw diameter D was 48, and extrusion granulation was carried out to obtain a PA6 / COC composite material.

[0075] Example 4

[0076] The present embodiment provides a PA6 / COC composite material, which comprises the following components by weight: PA6: 72.6 parts; COC: 20 parts; toughening agent: 5.0 parts; lubricant: 1.0 parts; antioxidant: 0.6 parts; modified filler: 7 parts; and nucleating agent: 0.8 parts.

[0077] The preparation method of the modified filler comprises the following steps:

[0078] (1) Alumina, titanium dioxide and silicon dioxide are mixed in a weight ratio of 1:0.5:1.6 to obtain a filler; the particle size of the aluminum oxide is 60-100 nm, and the specific surface area is 20-30 m2 / g; the particle size of the titanium dioxide is 30-50 nm, and the specific surface area is 15-30 m2 / g; the particle size of the silicon dioxide is 10-20 nm, and the specific surface area is 200-250 m2 / g;

[0079] (2) Under a nitrogen atmosphere, 3 parts by mass of polyethyleneimine and 9 parts by mass of water were mixed to obtain a polyethyleneimine aqueous solution. The polyethyleneimine aqueous solution was mixed with 1.2 parts by mass of a filler, stirred at 63° C. for 5.5 h, centrifuged, and dried to obtain a modified filler.

[0080] The preparation method of the composite material is as follows:

[0081] The formulated PA6 and COC, modified filler, toughening agent, lubricant, antioxidant and nucleating agent were mixed in a high-speed mixer for 4 minutes and then fed from the main feeding port of the twin-screw extruder, and the hollow glass microspheres were fed from the side feeding port of the twin-screw extruder. The temperature setting temperatures of each section of the twin-screw extruder were: 250°C, 250°C, 255°C, 255°C, 255°C, 260°C, 260°C, 265°C, 265°C, 260°C, the screw speed was set to 280rpm, the ratio of screw length L to screw diameter D was 48, and extrusion granulation was carried out to obtain a PA6 / COC composite material.

[0082] Comparative Example 1:

[0083] This comparative example provides a composite material, which comprises the following components in parts by weight: PA6: 98 parts; lubricant: 1.0 parts; antioxidant: 0.6 parts; modified filler: 7 parts; nucleating agent: 0.4 parts.

[0084] The preparation method of the modified filler comprises the following steps:

[0085] (1) Alumina, titanium dioxide and silicon dioxide are mixed in a weight ratio of 1:0.5:1.6 to obtain a filler; the particle size of the aluminum oxide is 60-100 nm, and the specific surface area is 20-30 m2 / g; the particle size of the titanium dioxide is 30-50 nm, and the specific surface area is 15-30 m2 / g; the particle size of the silicon dioxide is 10-20 nm, and the specific surface area is 200-250 m2 / g;

[0086] (2) Under a nitrogen atmosphere, 3 parts by mass of polyethyleneimine and 9 parts by mass of water were mixed to obtain a polyethyleneimine aqueous solution. The polyethyleneimine aqueous solution was mixed with 1.2 parts by mass of a filler, stirred at 63° C. for 5.5 h, centrifuged, and dried to obtain a modified filler.

[0087] The preparation method of the composite material is as follows:

[0088] The formulated PA6, modified filler, lubricant, antioxidant and nucleating agent were mixed evenly in a high-speed mixer for 4 minutes and then fed from the main feeding port of the twin-screw extruder, and the hollow glass microspheres were fed from the side feeding port of the twin-screw extruder. The temperature setting temperatures of each section of the twin-screw extruder were: 250°C, 250°C, 255°C, 255°C, 255°C, 260°C, 260°C, 265°C, 265°C, 260°C, the screw speed was set to 280rpm, the ratio of screw length L to screw diameter D was 48, and extrusion granulation was carried out to obtain a composite material.

[0089] Comparative Example 2:

[0090] This comparative example provides a composite material, which comprises the following components in parts by weight: PA6: 78 parts; COC: 20 parts; lubricant: 1.0 parts; antioxidant: 0.6 parts; modified filler: 7 parts; and nucleating agent: 0.4 parts.

[0091] The preparation method of the modified filler comprises the following steps:

[0092] (1) Alumina, titanium dioxide and silicon dioxide are mixed in a weight ratio of 1:0.5:1.6 to obtain a filler; the particle size of the aluminum oxide is 60-100 nm, and the specific surface area is 20-30 m2 / g; the particle size of the titanium dioxide is 30-50 nm, and the specific surface area is 15-30 m2 / g; the particle size of the silicon dioxide is 10-20 nm, and the specific surface area is 200-250 m2 / g;

[0093] (2) Under a nitrogen atmosphere, 3 parts by mass of polyethyleneimine and 9 parts by mass of water were mixed to obtain a polyethyleneimine aqueous solution. The polyethyleneimine aqueous solution was mixed with 1.2 parts by mass of a filler, stirred at 63° C. for 5.5 h, centrifuged, and dried to obtain a modified filler.

[0094] The preparation method of the composite material is as follows:

[0095] The formulated PA6 and COC, modified filler, lubricant, antioxidant and nucleating agent were mixed in a high-speed mixer for 4 minutes and then fed from the main feeding port of the twin-screw extruder, and the hollow glass microspheres were fed from the side feeding port of the twin-screw extruder. The temperature setting temperatures of each section of the twin-screw extruder were: 250°C, 250°C, 255°C, 255°C, 255°C, 260°C, 260°C, 265°C, 265°C, 260°C, the screw speed was set to 280rpm, the ratio of screw length L to screw diameter D was 48, and extrusion granulation was carried out to obtain a PA6 / COC composite material.

[0096] Comparative Example 3:

[0097] This comparative example provides a composite material, which comprises the following components in parts by weight: PA6: 93 parts; toughening agent: 5.0 parts; lubricant: 1.0 parts; antioxidant: 0.6 parts; modified filler: 7 parts; and nucleating agent: 0.4 parts.

[0098] The preparation method of the modified filler comprises the following steps:

[0099] (1) Alumina, titanium dioxide and silicon dioxide are mixed in a weight ratio of 1:0.5:1.6 to obtain a filler; the particle size of the aluminum oxide is 60-100 nm, and the specific surface area is 20-30 m2 / g; the particle size of the titanium dioxide is 30-50 nm, and the specific surface area is 15-30 m2 / g; the particle size of the silicon dioxide is 10-20 nm, and the specific surface area is 200-250 m2 / g;

[0100] (2) Under a nitrogen atmosphere, 3 parts by mass of polyethyleneimine and 9 parts by mass of water were mixed to obtain a polyethyleneimine aqueous solution. The polyethyleneimine aqueous solution was mixed with 1.2 parts by mass of a filler, stirred at 63° C. for 5.5 h, centrifuged, and dried to obtain a modified filler.

[0101] The preparation method of the composite material is as follows:

[0102] The formulated PA6, modified filler, toughening agent, lubricant, antioxidant and nucleating agent were mixed in a high-speed mixer for 4 minutes and then fed from the main feeding port of the twin-screw extruder, and the hollow glass microspheres were fed from the side feeding port of the twin-screw extruder. The temperature setting temperatures of each section of the twin-screw extruder were: 250°C, 250°C, 255°C, 255°C, 255°C, 260°C, 260°C, 265°C, 265°C, 260°C, the screw speed was set to 280rpm, the ratio of screw length L to screw diameter D was 48, and extrusion granulation was carried out to obtain a composite material.

[0103] Comparative Example 4:

[0104] This comparative example provides a composite material, which comprises the following components in parts by weight: PA6: 78 parts; COC: 20 parts; lubricant: 1.0 parts; antioxidant: 0.6 parts; modified filler: 7 parts; toughening agent: 5.0 parts.

[0105] The preparation method of the modified filler comprises the following steps:

[0106] (1) Alumina, titanium dioxide and silicon dioxide are mixed in a weight ratio of 1:0.5:1.6 to obtain a filler; the particle size of the aluminum oxide is 60-100 nm, and the specific surface area is 20-30 m2 / g; the particle size of the titanium dioxide is 30-50 nm, and the specific surface area is 15-30 m2 / g; the particle size of the silicon dioxide is 10-20 nm, and the specific surface area is 200-250 m2 / g;

[0107] (2) Under a nitrogen atmosphere, 3 parts by mass of polyethyleneimine and 9 parts by mass of water were mixed to obtain a polyethyleneimine aqueous solution. The polyethyleneimine aqueous solution was mixed with 1.2 parts by mass of a filler, stirred at 63° C. for 5.5 h, centrifuged, and dried to obtain a modified filler.

[0108] The preparation method of the composite material is as follows:

[0109] The formulated amount of PA6, COC, modified filler, toughening agent, lubricant and antioxidant were mixed in a high-speed mixer for 4 minutes and then fed from the main feeding port of the twin-screw extruder, and the hollow glass microspheres were fed from the side feeding port of the twin-screw extruder. The temperature setting temperatures of each section of the twin-screw extruder were: 250°C, 250°C, 255°C, 255°C, 255°C, 260°C, 260°C, 265°C, 265°C, 260°C, the screw speed was set to 280rpm, the ratio of screw length L to screw diameter D was 48, and extrusion granulation was carried out to obtain a PA6 / COC composite material.

[0110] Comparative Example 5:

[0111] This comparative example provides a composite material, which comprises the following components in parts by weight: PA6: 78 parts; COC: 15 parts; toughening agent: 5.0 parts; lubricant: 1.0 parts; antioxidant: 0.6 parts; filler: 7 parts; and nucleating agent: 0.4 parts.

[0112] The filler is a mixture of alumina, titanium dioxide and silicon dioxide in a weight ratio of 1:0.5:1.6. The particle size of alumina is 60-100nm, and the specific surface area is 20-30㎡ / g; the particle size of titanium dioxide is 30-50nm, and the specific surface area is 15-30㎡ / g; the particle size of silicon dioxide is 10-20nm, and the specific surface area is 200-250㎡ / g.

[0113] The preparation method of the composite material is as follows:

[0114] The formulated PA6, COC, filler, toughening agent, lubricant, antioxidant and nucleating agent were mixed in a high-speed mixer for 4 minutes and then fed from the main feeding port of the twin-screw extruder, and the hollow glass microspheres were fed from the side feeding port of the twin-screw extruder. The temperature setting temperatures of each section of the twin-screw extruder were: 250°C, 250°C, 255°C, 255°C, 255°C, 260°C, 260°C, 265°C, 265°C, 260°C, the screw speed was set to 280rpm, the ratio of screw length L to screw diameter D was 48, and extrusion granulation was carried out to obtain a PA6 / COC composite material.

[0115] Performance Testing

[0116] The composite materials in Examples 1-4 and Comparative Examples 1-5 were subjected to performance testing using ISO standards; solvent resistance test: a mechanical tensile test strip was placed at 135°C for 1000 hours to observe whether cracks appeared on the surface of the material and to calculate the performance retention rate; the selected solvent was a mixture of ethylene glycol solution and distilled water in a ratio of 1:1, and the test results are shown in Table 1 below.

[0117] Table 1: Comparative Table of Composite Material Performance Tests in Examples 1-4 and Comparative Examples 1-5

[0118]

[0119] From the results of Examples 1-4, it can be seen that since the density, tensile strength and impact strength of COC are slightly lower than those of PA6, with the increase of COC content, the density, tensile strength and simply supported beam notched impact strength of the material all decrease to a certain extent; the bending modulus basically does not change much; from the perspective of the solvent resistance specimen surface, there is little difference; from the perspective of the tensile strength retention rate of the material after the solvent resistance aging experiment, with the increase of COC content, while ensuring good compatibility between PA6 and COC, the solvent resistance of the material is greatly improved, indicating that COC helps to improve the solvent resistance and barrier properties of PA6 materials.

[0120] From the test results of comparative example 1, the tensile strength retention rate of pure PA6 after solvent aging is low, only 45.6%. In comparative example 2, in the absence of a toughening agent, the overall performance and solvent resistance of the material are poor. In this formula system, the toughening agent not only plays a toughening role, but also because its structure contains MAH and GMA functional groups, it can effectively act as a compatibilizer, so that PA6 and COC, which are incompatible in themselves, have a good compatibility, so that better mechanical properties and solvent resistance can be obtained. In comparative example 3, in the absence of COC, after adding a toughening agent, the impact strength of the material increases slightly, but the tensile strength and bending modulus of the material decrease to a certain extent; although the appearance of the spline after solvent aging has not changed significantly, the tensile strength of the material has a trend of further decrease. In the absence of a nucleating agent, the overall performance of the material in comparative example 4 decreases slightly, and the tensile strength retention rate after solvent resistance also decreases to a certain extent, but its impact strength increases slightly, indicating that the nucleating agent can play a role in improving the strength, solvent resistance and barrier properties of the material. In Comparative Example 5, the filler was not modified and had poor compatibility in the system of the present invention, resulting in a decrease in the overall performance of the material.

[0121] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0122] The applicant declares that the present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A high heat-resistant and high-barrier PA6 / COC composite material, characterized in that: The composite material comprises the following components by weight: 65-80 parts of PA6; 15-25 parts of COC; 6-10 parts of modified filler; Nucleating agent 0.3-0.8 parts; toughening agent 4-8 parts; lubricant 0.5-2 parts; antioxidant 0.2-1.0 parts; The preparation method of the modified filler comprises the following steps: (1) Alumina, titanium dioxide and silicon dioxide are mixed in a weight ratio of 1:0.4-0.6:1.5-1.7 to obtain a filler; the particle size of the aluminum oxide is 60-100 nm, and the specific surface area is 20-30 m2 / g; the particle size of the titanium dioxide is 30-50 nm, and the specific surface area is 15-30 m2 / g; the particle size of the silicon dioxide is 10-20 nm, and the specific surface area is 200-250 m2 / g; (2) under a nitrogen atmosphere, 3 parts by weight of polyethyleneimine and 8-10 parts by weight of water were mixed to obtain a polyethyleneimine aqueous solution, the polyethyleneimine aqueous solution was mixed with 1-1.5 parts by weight of a filler, stirred at 60-65° C. for 5-6 hours, centrifuged, and dried to obtain a modified filler; The content of MAH and GMA in the toughening agent is above 5%; The toughening agent is an E-GMA-MAH copolymer product.

2. The high heat-resistant and high-barrier PA6 / COC composite material according to claim 1, characterized in that: The intrinsic viscosity of the PA6 is above 3.0; the melt index of the COC is 10 g / 10 min-20 g / 10 min, and the test conditions are 260° C. and 2.16 kg.

3. The high heat-resistant and high-barrier PA6 / COC composite material according to claim 1, characterized in that: The antioxidant includes one or a combination of any of 2,6-di-tert-butyl-p-cresol, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tris(nonylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, dioctadecyl pentaerythritol diphosphite, dilauryl thiodipropionate, and pentaerythritol stearate.

4. The high heat-resistant and high-barrier PA6 / COC composite material according to claim 1, characterized in that: The lubricant includes any one of oxidized polyethylene wax, ethylene-propylene copolymer, and ethylene-vinyl acetate copolymer, or a combination of at least two of them.

5. The high heat-resistant and high-barrier PA6 / COC composite material according to claim 1, characterized in that: The nucleating agent includes P22 or CHB-3C.

6. A method for preparing the high heat-resistant and high-barrier PA6 / COC composite material according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: mixing the formulated amount of PA6, COC, modified filler, toughening agent, lubricant, antioxidant and nucleating agent in a high-speed mixer to obtain a mixture, feeding the mixture from the main feeding port of a twin-screw extruder, and performing extrusion granulation.

7. The method for preparing the high heat-resistant and high-barrier PA6 / COC composite material according to claim 6, characterized in that: The mixing time is 3 min-7 min; the ratio of the screw length to the screw diameter of the twin-screw extruder is 30-48; the control temperature of each section of the twin-screw extruder is 250° C.-270° C., and the rotation speed is 240 rpm-320 rpm.

8. The method for preparing the high heat-resistant and high-barrier PA6 / COC composite material according to claim 6, characterized in that: After extrusion granulation, the obtained particles are dried and then injection molded into standard specimens for testing using an injection molding machine; wherein the drying temperature is 100-120°C and the drying time is 4-6h; the control temperature of each section of the injection molding machine is 250°C-270°C and the screw speed is set to 100rpm-150rpm.

Citation Information

Patent Citations

  • Low-odor sterilization micro-bubbling scratching-resistant nylon composite material and preparation method thereof

    CN107903625A

  • Cycloolefin copolymer (COC) / PA composite and preparation method and application thereof

    CN110746768A